Role and place for railroad in the social and economic development of Tuva - Mongush, Mendi G. (The New Research of Tuva, 2012)
Article took the special prize in "Models for economic development of Tuva” essay contest held in 2012 by the Plenipotentiary Representative Office of Tuva in Moscow. Author reflects on social changes in Tuva, that will be brought by the completion of the railroad that will connect Tuva with the rest of Russia.
Keywords: Tuva; Russia; economy; investments; investment prospects; factors; society; railroad; Kyzyl – Kuragino